Viability-PCR for the selective detection of Lactobacillus acidophilus and Bifidobacterium bifidum in live bacteria-containing products - Catone, Stefania; Iannantuono, Serena; Genovese, Domenico; Von Hunolstein, Christina; Franciosa, Giovanna (Frontiers in Microbiology, 2024)
To exert their beneficial effects, microorganisms used in live bacteria-containing products must be viable and present in certain amounts. In this study, we developed a viability assay based on quantitative PCR coupled with propidium monoazide for the identification and enumeration of viable Lactobacillus acidophilus and Bifidobacterium bifidum. In order to optimize the protocol, the thermal inactivation conditions for the two target microorganisms and the PMA concentration inhibiting DNA amplification from the dead cells while allowing it from the live cells were first determined. The viability-PCR protocol was then applied to analyze a commercial product containing the two microorganisms. The quantities of both microorganisms determined using viability-PCR in the tested product were significantly higher than those obtained using the standard plate count, suggesting the presence of bacteria in a viable but nonculturable physiological state. Moreover, lower amounts of the two microorganisms were detected using viability-PCR compared to those achieved using quantitative PCR, possibly because of the presence of dead cells in the samples. Our results suggest that the viability-PCR method proposed here is a suitable alternative for rapid and accurate quantification and assessment of the viability of L. acidophilus and B. bifidum and could be easily adopted in the quality control screening of live bacteria-containing products.